Fatal feline leukemia virus-associated enteritis in a wild Eurasian lynx (Lynx lynx) in Germany - Gregor, Katharina Manuela; Mirolo, Monica; Brandes, Florian; Jesse, Sonja Tatjana; Kaiser, Franziska; Verspohl, Jutta; Wölfl, Sybille; Osterhaus, Albert D. M. E.; Baumgärtner, Wolfgang; Ludlow, Martin; Beineke, Andreas (Biology, 2024)
The Eurasian lynx (Lynx lynx), a widespread wild felid on the Eurasian continent, is currently classified as “critically endangered” in Germany. Understanding the impact of infectious agents is of particular importance for the continued conservation of these animals, especially regarding pathogens with broad host ranges and risk of interspecies transmission. Feline leukemia virus (FeLV) is known to infect wild and domestic felids worldwide, including several species of lynx, but it has not been reported thus far in the Eurasian lynx. In September 2020, a 16-month-old female Eurasian lynx from the Bavarian Forest, Germany, showed a sudden onset of gastrointestinal signs such as anorexia, diarrhea, and vomiting, and died within one week. Macroscopic and histologic examination revealed hemorrhagic-necrotizing enteritis and typhlocolitis, with the degeneration of crypts and crypt abscesses, as well as depleted Peyer’s patches. In addition, the animal showed lymphoid depletion (lymph nodes, thymus, and spleen) and hypocellularity of the bone marrow. FeLV infection was confirmed by immunohistochemistry and next generation sequencing. A secondary bacterial infection with hemolytic Escherichia coli and Clostridium perfringens type A was present in the intestine. This is the first report of FeLV-associated enteritis, lymphoid depletion and bone marrow suppression with associated secondary bacterial infection in a Eurasian lynx.